Intrathecal Synthesis of Oligoclonal Bands in Rapid-Onset Obesity With Hypothalamic Dysfunction, Hypoventilation, and Autonomic Dysregulation Syndrome: New Evidence Supporting Immunological Pathogenesis. (March 2014) - Sartori, Stefano; Priante, Elena; Pettenazzo, Andrea; Marson, Piero; Suppiej, Agnese; Benini, Franca; Perilongo, Giorgio; Toldo, Irene
Rapid-onset obesity with hypothalamic dysfunction, hypoventilation, and autonomic dysregulation syndrome (ROHHADS) is a rare, but potentially lethal, pediatric disorder. To date, nearly 80 patients have been reported in the literature; however, the etiopathogenesis is still unclear and debated. Both genetic and paraneoplastic or immune-mediated causes have been supposed to be involved in this syndrome. Nonetheless, at this time, a diagnostic biomarker is not available and diagnosis is based exclusively on clinical criteria. Aiming to establish the immune-mediated pathogenesis, we report 2 children with a clinical picture consistent with ROHHADS and whose cerebrospinal fluid analysis disclosed an intrathecal synthesis of oligoclonal bands. Even if many aspects remain to be explained, this finding suggests that ROHHADS could share similar pathogenetic mechanisms with other immune-mediated central nervous system disorders, and even more important, it might pave the way to a therapeutic chance for these patients by means of immunotherapy.